PENDIDIKAN ANAK USIA DINI (PAUD) DI KECAMATAN PERCUT SEI TUAN - Damaiwaty Ray; Misgiya .; Linda Aruan (Universitas Negeri Medan, 2017)
Abstract: Early Childhood Education in Percut Sei Tuan. By the problems the which being faced, then an action or solution is taken to overcome the problems of partners namely: providing training, guidance, and mentoring integrated to teachers ECD Al-Fajri and ECD Rahmatul Iman in District Percut Sei Tuan in the preparation of the Action Weekly Plan ( RKM), Daily Activity Plan (RKH), manufacture instructional media, teaching methods and educational games. The method which is used is education, training and mentoring, and practicing. The purpose of this IbM activity is to enhance the knowledge and skills of teachers of early childhood development partner in the preparation of RKM, RKH, manufacture instructional media, teaching methods, and designing educational games.Keywords: Early Childhood Education. Abstrak: Pendidikan Anak Usia Dini (PAUD) di Kecamatan Percut Sei Tuan. Metode yang digunakan adalah pendidikan, pelatihan dan pendampingan, dan peraktek. Adapun tujuan dari kegiatan IbM ini adalah untuk meningkatkan pengetahuan dan keterampilan guru-guru PAUD mitra dalam pengembangan penyusunan RKM, RKH, pembuatan media pembelajaran, metode pengajaran, dan mendesain permainan edukatif. Berdasarkan data yang diperoleh guru-guru PAUD di Desa Kolam dan Desa Bandar Setia telah mampu menyusun RKM, RKH, pengembangan media pembelajaran, metode pengajaran, dan permainan edukatif untuk meningkatkan motorik kasar anak dan mengaplikasikannya di depan kelas (Real Teaching) dengan baik. Kata kunci: Pendidikan Anak Usia Dini